2017
DOI: 10.1002/adv.21863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical recycling simulation of polylactide using a chain extender

Abstract: This work studied the commercial chain extender effectiveness on the mechanical recycling simulation of a pristine PLA using a single-screw extruder. We processed the material by two extrusion cycles to simulate a recycling process. In the second extrusion, part of the material was processed with chain extender and we evaluated its molecular weight, thermal degradation, melt flow index (MFI), thermal transitions, and mechanical properties. The molecular weight for the extruded neat PLA decreased and the MFI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 33 publications
5
45
0
3
Order By: Relevance
“…This result indicated that the extruded PLA exhibited increased melt flow ability or reduced melt viscosity, which may be due to the reduction in the molecular weight while undergoing high temperature and shear. Cosate de Andrade et al 29 reported that the molecular weight (M w ) of PLA decreased from 183,000 g/mol to 132,000 g/mol after one‐time extrusion, and its MFI significantly increased from 8 g/10 min to 21 g/10 min because of the thermal and shear degradation. Blending PLA with TPSN caused reduced MFI (Figure 1(c)) when compared with the extruded PLA (Figure 1(b)), implying a higher melt viscosity because of the highly entangled starch polymers in TPS melts 30 .…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated that the extruded PLA exhibited increased melt flow ability or reduced melt viscosity, which may be due to the reduction in the molecular weight while undergoing high temperature and shear. Cosate de Andrade et al 29 reported that the molecular weight (M w ) of PLA decreased from 183,000 g/mol to 132,000 g/mol after one‐time extrusion, and its MFI significantly increased from 8 g/10 min to 21 g/10 min because of the thermal and shear degradation. Blending PLA with TPSN caused reduced MFI (Figure 1(c)) when compared with the extruded PLA (Figure 1(b)), implying a higher melt viscosity because of the highly entangled starch polymers in TPS melts 30 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand mechanical recycling causes downgrading so the recycled PLA will be of a lower quality that if it was chemically recycled [53]. When mechanically recycling PLA, it is possible to add a chain extender which helps partially recover the impaired molar mass and other mechanical properties, making the recycled PLA more comparable with virgin PLA [54]. Niaounakis [55] estimated that in order for a specific biopolymer packaging and postconsumer mechanical recycling plant to be profitable, there needs to be a global production of at least 200 kT of biopolymer and the recycling facility should be able to process at least 5-18 kT annually.…”
Section: Mechanical Recyclingmentioning
confidence: 99%
“…This difference is caused by degradation of the biopolymer during the recycling process, which reduces the molar mass of the material. The shorter polymer chains have increased mobility, which allows them to rearrange into crystalline structures and crystallize at lower temperatures [ 65 ].…”
Section: Resultsmentioning
confidence: 99%